Avaliação espaço-temporal da qualidade da água e simulação de autodepuração na bacia hidrográfica do córrego São Simão, SP - Gonçalves, Julio César De Souza Inácio; Sardinha, Diego De Souza; Souza, Antonio Donizetti Gonçalves De; Dibiazi, André Luis Bigaram; Godoy, Letícia Hirata [UNESP]; Conceição, Fabiano Tomazini Da [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrográficas, 2012)
This study evaluated the water of São Simão stream watershed. For this, six sampling points were established and twelve samples of water were collected during the months of March, May, June, July, August, September, October, November, and December of 2005 and January, February, and March of 2006. The following variables were analyzed: discharge, temperature, turbidity, pH, electrical conductivity (EC), dissolved oxygen (DO), alkalinity, chloride and TSS (total suspended solids). The Streter & Phelps model which correlates the variation of the deficit oxygen with the distance was applied to evaluate the São Simão stream auto-purification. The characteristics of the São Simão stream near its spring until it reaches São Simão city allowed concluding that there is low interference in its quality. However, the absence of treatment of domestic wastewater at São Simão city reduced the water quality and increased the degradation process of São Simão stream after passing through the city. The Streeter & Phelps model allowed identifying the auto-purification zones in this stream and indicated the need for primary wastewater treatment, with an efficiency of 30%.

Neste trabalho foram avaliadas as águas fluviais da bacia hidrográfica do córrego São Simão (SP). Para isso, seis pontos de coleta foram estabelecidos e realizaram-se doze coletas de água durante os meses de março, maio, junho, julho, agosto, setembro, outubro, novembro e dezembro de 2005, e janeiro, fevereiro e março de 2006, analisando as seguintes variáveis: vazão, temperatura, turbidez, pH, condutividade, oxigênio dissolvido, alcalinidade, cloreto e sólidos totais em suspensão. A simulação do processo de autodepuração foi realizada com o uso do modelo de Streeter-Phelps, o qual relaciona a variação do déficit de oxigênio dissolvido com o perfil longitudinal do rio. As características do córrego São Simão próximo à sua nascente até a cidade de São Simão permitem concluir que há pouca interferência na sua qualidade. Porém, a falta de tratamento para o esgoto doméstico na cidade de São Simão piora a qualidade da água e intensifica o processo de degradação do córrego São Simão. O modelo de Streeter & Phelps permitiu identificar as zonas de autodepuração do córrego São Simão e indicou a necessidade de tratamento de esgotos em nível primário, com eficiência de 30%.
Water quality spatial and temporal evaluation and auto-purification simulation from the São Simão stream watershed, SP
Keywords: Avaliação da qualidade da água; esgotos domésticos; modelagem matemática de autodepuração; Water quality evaluation; waste water; auto-purification mathematical modeling